The Testimony of the Anonymous Cleric about the Hospital of Saint John of God in Jerusalem (1177-1187) (Circe de clásicos y modernos, 2018)
Since its origins, the work of care and attention to the poor and the sick defined the sense and the particular character of the Order of the Knights Hospitallers of Jerusalem. The emblem of this work was the hospital that the Order built in the Holy Land. Indeed, the Testimony of the Anonymous Cleric –written sometime between the years 1177 and 1187– constitutes the most important description in extenso of the medical work developed in the Hospital of Saint John. For this reason, in this article we present the first translation into Spanish of the original Latin text, edited on the basis of the only manuscript that is preserved of this text (Clm4620, fols. 132v°-139v°).
Keywords: Hospital; Jerusalem; Hospitallers; Testimony of the Anonymous Cleric; translation